Systems Development and Trade Union Activities - Kyng, Morten; Mathiassen, Lars (DAIMI Report Series, 1980)
Systems development is the process of constructing or modifying edp- based systems as a means of changing organizations. Since the early seventies Scandinavian trade unions have initiated a number of research projects within the field of edp-based systems and systems development as part of their endeavours to gain control over technological development. This paper contains a survey of these research activities. It describes the research methods applied. Edp- based systems and systems development are then discussed from a trade union point of view. Finally the research projects are related to other trade union activities and to activities within research and educational institutions.